The Institutional Nature of Complaints in Market and Distributional Environments - Bessonova, Olga (Journal of Economic Sociology, 2022)
This paper is based on the polemics with the author of the article “Complaints are not Gifts. Dysfunctionality of the Institution of Complaints in the Field of Housing and Communal Services in Russia.” The main focus of polemics is the conceptualization of the subject of research. The main thesis of “Complaints are not gifts” follows the widely accepted view that as a feedback mechanism, the institution of complaints is ineffective. The common mistake in the study of complaints is narrowing the consideration of complaints to their socio-psychological aspects, appealing to behavioral characteristics and the concept of ‘Russian mentality,’ and ignoring the very institutional nature of complaints as the most important element of the hierarchical system of management. The “Complaints are not gifts” fails to eschew this blunder. In the present article, I will reveal the essential characteristics of the institution of complaints, and explain why this institution has been rationalized and supported by the authorities throughout the historical development of the Russian socio-economic system. I will also review the complaints that formed the empirical data for the “Complaints are not gifts” article. These complaints are used by the Russian housing and utilities management companies as a template if they choose a competitive market strategy of complaining against their clients. Finally, I will review the prospects for the institution of complaints in Russia. Apart from the general expansion of the institution of complaints, we can expect its digitalization and the creation of state portals in the regions for receiving complaints. These will not, however, change the institutional nature of complaints. The institutional environment in Russia is gradually moving away from the market forms of governance to the system of “razdatok”, or central distribution system characteristic of the USSR period. Considering this, and also the fact that the state segment makes up to eighty percent of the entire Russian economy today, private utility service companies will have to adapt more actively to the experience of using customer complaints to survive in this environment.